Oxygen-Defects Functionalized Graphite Nanoplatelets as Electrode Materials for Electrochemical Sensing. Issue 15 (24th October 2019) - Zhu, Xiaohua; Wu, Can; Miao, Liqiong; Zhang, Yanyu; Cheng, Shengming; Liang, Yong; Nan, Junmin
Abstract : The electrocatalytic role of oxygenated defects in graphite nanoplatelets (GNPs) was evaluated to advance the nanosized graphite as an alternative modified matrix in electrochemical sensors. The oxidized GNPs (ox-GNPs) were prepared via a ball milling and oxidizing process. The abundant functional groups and defective sites in the ox-GNPs result in the excellent electrocatalytic activity compared with GNPs. The redox behaviors of hydroquinone and catechol at the ox-GNPs modified glassy carbon electrode (ox-GNPs/GCE) were investigated. Compared to GNPs/GCE, the as-prepared ox-GNPs/GCE exhibited enhanced electrocatalytic activity and well-define redox peaks. The detection limit was 0.4 and 0.6 μM for hydroquinone and catechol, respectively (S/N = 3). In addition, this ox-GNPs/GCE also shows potential applications to the practical sample and some important biomolecules. The as-prepared ox-GNPs/GCE all can exhibit efficient sensitivity for the electrochemical determination of neurotransmitters (ascorbic acid and dopamine), nucleic acid bases (guanine), pharmaceuticals (rutin and thymol), and other biological molecules (uric acid). These results demonstrate the potential of nanosized graphite material in sensing applications.